1986
DOI: 10.7557/2.6.2.649
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow and kidney fat as indicators of condition in reindeer

Abstract: Back-fat depth, kidney-fat index (KFI), fat and triglyceride contents in femur and metatarsal marrows were measured from 92 semi-domesticated reindeer (Rangifer tarandus tarandus L.) in northern Finland during 1980-84. The age of the reindeer varied from 5 months to 10 years and marrow fat content was estimated by five different methods: standard ether extraction, oven-drying (Neiland, 1970), reagent-dry assay (Verme and Holland, 1973), compression method (Greer, 1968) and visual estimation (Cheatum, 1949). Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
0

Year Published

1990
1990
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 17 publications
1
22
0
Order By: Relevance
“…Foragers seem to be well aware of this phenomenon, as they have been observed to use marrow characteristics to evaluate the nutritional condition of killed animals (for a Nunamiut example see Binford [1:187], for a Hadza example see Bunn et al [8:427]). Reports on caribou marrow suggest that fat is mobilized first in proximal (femur and humerus) bones of the legs [9,14,31]. However, there is no clear sequence of fat mobilization between the mid leg bones (tibia and radio-ulna) and bones from the extremities (metapodials) in caribou.…”
Section: Discussionmentioning
confidence: 99%
“…Foragers seem to be well aware of this phenomenon, as they have been observed to use marrow characteristics to evaluate the nutritional condition of killed animals (for a Nunamiut example see Binford [1:187], for a Hadza example see Bunn et al [8:427]). Reports on caribou marrow suggest that fat is mobilized first in proximal (femur and humerus) bones of the legs [9,14,31]. However, there is no clear sequence of fat mobilization between the mid leg bones (tibia and radio-ulna) and bones from the extremities (metapodials) in caribou.…”
Section: Discussionmentioning
confidence: 99%
“…Possible markers of body condition of reindeer are the depots of body fat (e.g. Nieminen & Laitinen, 1986) and the content of the reticulo-rumen (Adamczewski et al, 1987). Data from a simultaneous study (Nilsson et al, 1996b), makes it possible to compare the initial condition and the subsequent performance of the free-ranged calves recruited in January 1995 for the present study with calves taken from the same herd in September 1994.…”
Section: Discussionmentioning
confidence: 99%
“…Probably because of this preference, it has been reported that volumetric calculations were made by extraction method to predict the amount of bone marrow in distal extremities [13,14]. However, stereological methods are considered as a more acceptable scientific approach for these calculations [15,18], because the classical methods revealed some difficulties such as injecting fluid to the cavity of bone. By using Cavalieri principle, which is a stereological method, not only the volume of bone marrow but also volume of the bone can be calculated.…”
Section: Resultsmentioning
confidence: 99%